2005
DOI: 10.1007/s11104-004-1310-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nitrogen mineralization in mowed or glyphosate treated cover crops compared to direct incorporation

Abstract: Information on how management by mowing and herbicide alter residue quality and nitrogen (N) inputs would be valuable to improve prediction of N availability. Mowing and glyphosate application are widely used by growers to limit cover crop growth and facilitate incorporation. A mixture of cover crops, hairy vetch (Vicia villosa L.), oriental mustard (Brassica juncea L.) and cereal rye (Secale cereale L.), was investigated as a means to improve soil quality and optimize N availability. There is limited informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 25 publications
5
31
1
Order By: Relevance
“…Consequently, as the amount of mineralizable N in the soil was higher, the inorganic N soil content in PIBS was higher than in the other treatments. Snapp and Borden (2005) found the same trend when rye residues were incorporated after mowing: the N mineralization rate was higher than in bare soil 3 weeks after incorporation. Moreover, Corbeels et al (2003) observed that burying crop residues could maintain N fertility in the long term.…”
Section: Discussionsupporting
confidence: 59%
“…Consequently, as the amount of mineralizable N in the soil was higher, the inorganic N soil content in PIBS was higher than in the other treatments. Snapp and Borden (2005) found the same trend when rye residues were incorporated after mowing: the N mineralization rate was higher than in bare soil 3 weeks after incorporation. Moreover, Corbeels et al (2003) observed that burying crop residues could maintain N fertility in the long term.…”
Section: Discussionsupporting
confidence: 59%
“…Despite the moderate quantities of mustard residues incorporated, N mineralization potential pool responded; presumably due to the high N content of mustard tissues relative to rye tissues (Table 3). An earlier study of cover crop management supported these findings, as residue quality was the driving factor in N mineralization response of large cores from a related potato systems trial (Snapp and Borden 2005).…”
Section: Rye Versus Mustardmentioning
confidence: 65%
“…For example, Brassica residues have been shown to alter the soil nematode community structure, which in turn profoundly affects the soil microbial food web, as indicated by studies of biosuppressive effects on plant parasitic nematodes such as Pratylenchus penetrans (Porter et al 1998). Though the level of nitrogen (N) immobilization or release from residues depends on residue quality and other environmental factors, N cycling by Brassicas can influence soil microbial activity and main crop growth (Snapp and Borden 2005). Because of their potential as both a cover and oilseed crop, farmers are particularly interested to know the potential effects of incorporating different rates and types (roots versus shoots) of Brassica tissues on disease suppression and root health within typical field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The stimulation of microorganisms and their activities due to the application of herbicides brought about greater mineralization of organic nitrogen resulting in greater amount of available nitrogen (Snapp and Borden 2005) and subsequent loss of nitrogen from soil due to volatilization by the microorganisms (Smith and Weeraratna 1974; Tables 3 and 4). In general, application of pendimethalin and quizalofop either alone or in combination retained higher amount of total nitrogen as compared to untreated control (Table 3).…”
Section: Resultsmentioning
confidence: 99%